Prevention of Sexually Transmitted Infectious Diseases (STI), HIV AIDS Based Onottawa Charter Health Promotion Strategy in Wakatobi District, Southeast Sulawesi - Andi Asrina; Fairus Prihatin Idris; Muhammad Ikhtiar (Global Health Science Group, 2022)
Targeting to end the AIDS Epidemic by 2030, the government of Wakatobi Regency, Southeast Sulawesi undertakes HIV prevention efforts with Health promotion strategies based on the Ottawa Charter so that individuals and communities can adopt healthy behaviors by not behaving at risk. This study aimed to examine the prevention of STIs and HIV AIDS based on the Ottawa Charter in Wakatobi in 2022. Using Quasi qualitative data collection techniques using observation, in-depth interviews, and documentation. Informants, namely 1 key informant: Head of the Wakatobi District Health Office, 1 Supporting Informant is the Wakatobi KPAD, and 3 regular informants, namely the Head of Division and Head of the Prevention and Control of Infectious Diseases and Public Health Center officers in Wakatobi Regency. Based on the study results, shows that prevention efforts based on the Ottawa strategy have been implemented but have not been maximized. There are several dimensions: health-oriented policies, a supportive environment, Reorientation of Health Services, individual skills strategies, and Community Movements. Although not many activities have been carried out related to independent programs in HIV prevention and control, the Health Office and KPAD have included plans to approach existing risk groups so that they can realize positive behaviors for health. Based on the results of the study, HIV AIDS Prevention Efforts in Wakatobi Regency based on the Ottawa Charter still need to be improved and strengthened by the local government, especially the Health Service and KPAD. Several programs are still in the planning stages within the dimensions of the Ottawa Charter.